Intervensi Terapi Musik dapat Meningkatkan Fungsi Kognitif pada Lansia - Wahyuni, Anyta Hera; Rekawati, Etty; Kurnia, Dikha Ayu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to identify the effect of music therapy interventions on cognitive function in elderly people in nursing homes. The method used in this research was a systematic review using a systematic search through the ProQuest, Clinical Key Nursing, PubMed, Sage journal, and Scopus databases with articles that met the inclusion criteria with publications between 2014 and 2023, as well as an article search technique using the PRISMA scheme stages. The results of this study show that the search results identified ten articles in which various types of music therapy interventions and durations of interventions stated that music therapy had a positive effect on the cognitive function of the elderly. The conclusion obtained is that music therapy interventions can be effective interventions to improve cognitive function in the elderly.